Effect of Different Leachate/Acetate Ratios in a Submerged Anaerobic Membrane Bioreactor (SAnMBR) - Taskan, Ergin; Hasar, Halil (Wiley, 2012)
Leachate treatment using a membrane bioreactor is an effective method. This study presents a configuration including an anaerobic bioreactor and a membrane module, called submerged anaerobic membrane bioreactor (SAnMBR), for treating influent with leachate/acetate rations (L/A), that were kept to be 10, 25, 50, 75, and 100% at a constant SRT (100 days). COD removal decreased from 85 to 75% when the L/A ratio increased from 10 to 100. To prevent membrane fouling, a SAnMBR was operated in the case of circulation of mixed liquor under continuous and intermittent suction. The average fluxes were 2.60 and 0.40?L/m2?h at the periods of intermittent and continuous suction, respectively. The methane production varied between 0.25 and 0.32?L CH4/g CODremoved.
Keywords: Chemical oxygen demand; Landfill; Membrane fouling; Methane production rate; Methanogens